Model Rekrutmen Direksi dan Komisaris yang Mandiri dan Akuntabel pada Perusahaan Perseroan dalam Kerangka Hukum BUMN di Indonesia - Antoni, Antoni (Universitas Batanghari Jambi, 2024)
One of the keys to the success of a company, whether private or government owned, cannot be separated from the people who will lead the company. As is the case with BUMN directors and commissioners, they are people who struggle to bring the company to better development. Therefore, in order to find a leader, whether a director or commissioner, it will really depend on what model is used in the recruitment. With the right recruitment model, it is hoped that it can reduce or even eliminate various aspects of certain interests that can arise from the positions that will be held by company leaders (directors and commissioners). The form of recruitment must reflect a form that truly provides clear, clear boundaries regarding the rights and roles of effective, efficient and accountable clarity in accordance with the principles of good corporate governance (GCG). As a result, there is legal clarity and equality for all in conditions of economic progress.